2013
DOI: 10.1111/1758-2229.12126
|View full text |Cite
|
Sign up to set email alerts
|

Stability of soil microbial structure and activity depends on microbial diversity

Abstract: Despite the central role of microbes in soil processes, empirical evidence concerning the effect of their diversity on soil stability remains controversial. Here, we addressed the ecological insurance hypothesis by examining the stability of microbial communities along a gradient of soil microbial diversity in response to mercury pollution and heat stress. Diversity was manipulated by dilution extinction approach. Structural and functional stabilities of microbial communities were assessed from patterns of gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 152 publications
(82 citation statements)
references
References 60 publications
5
77
0
Order By: Relevance
“…This is consistent with the negative relationship between fungal richness and amended-soil mineralisation. Such negative relationships were unexpected, as previous studies demonstrated positive relationships [6,7,49]. Nevertheless, the negative relationship does not necessarily contradict these studies, which focused on total flux.…”
Section: Discussionmentioning
confidence: 59%
“…This is consistent with the negative relationship between fungal richness and amended-soil mineralisation. Such negative relationships were unexpected, as previous studies demonstrated positive relationships [6,7,49]. Nevertheless, the negative relationship does not necessarily contradict these studies, which focused on total flux.…”
Section: Discussionmentioning
confidence: 59%
“…This property might help to maintain the stability of soil microbial activity28 and to sustain the SOC and TN in alpine grassland soils. Based on these observations, we reject our first hypothesis that soil biochemistry (including soil nutrients and microbiological activities) in alpine grasslands would be altered by climate change and yak overgrazing over a short time period.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent paper (78) created a microbial diversity gradient using a dilution series and found that increased diversity enhanced community structural (i.e., composition) stability when exposed to heat stress and mercury pollution. Diversity also conferred functional (soil respiration) stability toward heat stress, but not mercury pollution, suggesting that the effect of diversity may be stress type dependent (78). Similarly, another study investigated the effect of benzene and mercury pollution on microbial community stability and functioning but using soils that naturally differed in bacterial diversity (79).…”
Section: Soil Biodiversity Resistance and Resiliencementioning
confidence: 99%